(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Adverse Drug Reactions (ADRs) underreporting is a great challenge to pharmacovigilance. Healthcare professionals should consider ADR reporting as their professional obligation because the effective system of ADR reporting is important to improve patient care and safety. This study was designed to assess the knowledge, attitude, practice and factors associated with ADR reporting by healthcare professionals (physicians and pharmacists) in secondary and tertiary hospitals of India.